Integrating innovation and technology in enhancing teaching and learning entrepreneurship education in public universiti of higher learning - Wahid, Ahzilah; Ibrahim, Amlus; Hashim, Norashidah; Chandra, Punitha (2015)
This article studies to improve innovation and innovation in entrepreneurship education reveals the need for engaging teaching methods in this field.Entrepreneurship education has been measured one of the main instruments for improving the entrepreneurial attitude of both potential entrepreneurs and new growth.Some researchers have found that exposure to technology in entrepreneurship education widespread increase entrepreneurial intentions participants.Several empirical studies find methods of teaching and learning approach using technology integration will enhance the entrepreneurial intentions among students. Technology Entrepreneurship Education is not only about the transfer of knowledge, but also facilitate the creation of knowledge; and it is not just about cognitive knowledge of a scientific field, but also the ability to find new opportunities and venture creation process.